Perfect competition in A.-R.-J. Turgot: A contractualist theory of just exchange - José Manuel Menudo (Duke University, Center for the History of Political Economy (CHOPE), 2010)
This paper analyses one of Turgot's first economic essays, Plan d'un ouvrage sur le commerce, la circulation et l'intérêt de l'argent, la richesse des états (1753-4). Written prior to the appearance of physiocratic influence, it is Turgot's contribution to the movement of writing that bubbled up around the general issue of the market as mechanism of allocation generated by Vicent de Gournay. The wide conceptual apparatus - cognitive models and a series of interdisciplinary analytical tools -, employed by Turgot in the analysis of social problems, is integrated into this particular context. Given this widespread interpretation, the conclusion is reached that Turgot created a theory of just exchange on the basis of a contractualist approach. The behavioural hypothesis introduced by Turgot into exchange provides an alternative response to the dilemma posed by the rule of equal gain for the uniqueness of price and to which the literature has responded with the assumption of symmetric or transparent agents.
Keywords: B11; A12; B41; D63; D81; 330; Turgot; Relation of Economics to Other Disciplines; Price formation; Equity; Justice; Inequality; Criteria for Decision-Making